Confinement and Resistance in Banira Giri’s Novel The Prison - Sharma, Bimala (Karnali Outlook: Knowledge Across Disciplines, 2026)
This research paper investigates Banira Giri’s novel The Prison from the perspectives of existential dilemmas, gender oppression, and socio-political restrictions imposed on women. The paper examines how the protagonist can navigate through individual and societal restrictions using the lenses of existential feminism. To unveil these aspects, the paper seeks to answer these research questions: How does The Prison portray existentialist themes? In what ways does The Prison serve as a feminist critique of Nepali society, and how does Giri’s narrative style enhance the themes of confinement and resistance? The objective of this paper is to analyze the existentialist themes in the text, to examine how the novel critiques gender oppression and socio-political constraints on women in Nepali society, and to explore how Giri’s narrative style—through symbolism, metaphor, and structure, enhances the themes of confinement and resistance. This study uses a qualitative research method, using textual analysis to explore the novel’s themes, symbols, and narrative style. Existential feminism has been employed as an analytical lens. The analysis is set in three parts: existentialist themes in The Prison, feminist critique of Nepali society, and narrative structure and the themes of confinement and resistance. Findings prove existentialist struggles and alienation, the theme of confinement and freedom and symbolism and metaphors used in the existentialist context.